2005
DOI: 10.1099/vir.0.80440-0
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus latent membrane protein 2A mimics B-cell receptor-dependent virus reactivation

Abstract: Latent membrane protein 2A (LMP2A) of Epstein-Barr virus (EBV) shares protein motifs with the B-cell receptor that play a role in B-cell receptor signalling and has been shown to mimic an activated B-cell receptor by providing a survival signal for mature B cells in transgenic mice. Conversely, LMP2A has been reported not to support but to inhibit B-cell receptor signalling with respect to virus reactivation and to block lytic virus induction after anti-Ig treatment of EBV-infected B cells. To solve this appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…The possibility that LMP2A promotes plasma cell differentiation is interesting, in that Thorley-Lawson and colleagues have provided evidence that lytic reactivation requires differentiation into plasma cells (15). When combined with recent evidence that LMP2A may act as a BCR mimic to promote lytic reactivation (27), the data together suggest that LMP2A may be important for viral reactivation by promoting plasma cell differentiation when stimulated through the BCR and CD40.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The possibility that LMP2A promotes plasma cell differentiation is interesting, in that Thorley-Lawson and colleagues have provided evidence that lytic reactivation requires differentiation into plasma cells (15). When combined with recent evidence that LMP2A may act as a BCR mimic to promote lytic reactivation (27), the data together suggest that LMP2A may be important for viral reactivation by promoting plasma cell differentiation when stimulated through the BCR and CD40.…”
Section: Discussionmentioning
confidence: 69%
“…More recent studies indicate that LMP2A may allow BCR signaling (28) and even act as a BCR mimic to induce lytic reactivation (27). Therefore, additional models are needed to dissect the effect of LMP2A on B cells.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of LMP2B may be essential at this phase of the virus life cycle to regulate LMP2A activity to ensure that cells do not undergo lytic replication. In particular, previous studies have suggested that LMP2A expression can activate virus lytic replication (87). Thus, the strength of the LMP2A signal may have very diverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…32 LMP2A has been reported to prevent EBV-infected cells from entering the lytic and productive phase of EBV's life cycle, 11 but this issue is controversial. 33,34 We therefore asked whether in vitro, growth-transformed LCLs depend on sustained LMP2A signaling. Mixed populations of BCR ϩ/Ϫ primary B cells were infected with 2190 EBV, which carries its LMP2A allele flanked by 2 loxP sites ( Figure 2A) or with 2089 WT EBV.…”
Section: Sustained Lmp2a Expression Prevents Apoptotic Death Of In VImentioning
confidence: 99%